Acquisition of Streptococcus pneumoniae in South African children vaccinated with 7-valent pneumococcal conjugate vaccine at 6, 14 and 40 weeks of age. Issue 5 (29th January 2015) - Nunes, Marta C.; Jones, Stephanie A.; Groome, Michelle J.; Kuwanda, Locadiah; Van Niekerk, Nadia; von Gottberg, Anne; de Gouveia, Linda; Adrian, Peter V.; Madhi, Shabir A.
Abstract Background Seven-valent pneumococcal conjugate vaccine (PCV7) was introduced into the South African immunization program using 6, 14 and 40 weeks dosing schedule (2 + 1), with no catch-up in older children since April 2009. We investigated pneumococcal colonization acquisition in children who received this schedule and also compared it to historical cohorts of PCV-naïve children (n = 123 in 2007) and children who received a 3 + 1 PCV7 schedule (n = 124 in 2005/06). Methods Two hundred and fifty children aged 6–12 weeks were enrolled from December 2009 to April 2010. Participants had nasopharyngeal swabs collected on eight occasions between enrolment and 2-years of age. Standard methods were undertaken for bacterial culture and Streptococcus pneumoniae were serotyped using the Quellung method. Pneumococcal and Staphylococcus aureus colonization in the present study was compared to colonization in two historical longitudinal cohorts. Results S. pneumoniae was identified in 1081 (61.4%) of 1761 swabs collected in the current cohort. Pneumococcal colonization peaked at 41-weeks of age (76.8%) and decreased to 62.8% by 2-years of age (p = 0.002); PCV7-serotype colonization decreased during the same period from 28.6% to 15.6% (p = 0.001). Children from the current cohort compared to PCV-naïve children were less likely to be colonized by PCV7-serotypes from 40-weeks to 2-years of age and acquired PCV7-serotypes less frequently. No differences in overall pneumococcal, PCV7-serotype and non-PCV7-serotype colonization or new serotype acquisitions were detected comparing the current cohort to the historical cohort who received the 3 + 1 PCV7 schedule. Staphylococcus aureus colonization was similar in all three cohorts. Conclusion A 2 + 1 PCV7 schedule implemented in South Africa was temporally associated with reduced risk of vaccine-serotype colonization compared to historically unvaccinated children. Also, vaccine-serotype acquisition rate using the 2 + 1 schedule was similar to that in the 3 + 1 dosing cohort, suggesting that similar indirect protection against pneumococcal disease could be derived from either schedule in South Africa.